Development of transgenic Brassica juncea lines for reduced seed sinapine content by perturbing phenylpropanoid pathway genes - Kajla, Sachin (PLoS One, 2017)
Sinapine is a major anti-nutritive compound that accumulates in the seeds of Brassica species. When ingested, sinapine imparts gritty flavuor in meat and milk of animals and fishy odor to eggs of brown egg layers, thereby compromising the potential use of the valuable protein rich seed meal. Sinapine content in Brassica juncea germplasm ranges from 6.7 to 15.1 mg/g of dry seed weight (DSW) which is significantly higher than the prescribed permissible level of 3.0 mg/g of DSW. Due to limited natural genetic variability, conventional plant breeding approach for reducing the sinapine content has largely been unsuccessful. Hence, transgenic approach for gene silencing was adopted by targeting two genes—SGT and SCT, encoding enzymes UDP- glucose: sinapate glucosyltransferase and sinapoylglucose: choline sinapoyltransferase, respectively, involved in the final two steps of sinapine biosynthetic pathway. These two genes were isolated from B. juncea and eight silencing constructs were developed using three different RNA silencing approaches viz. antisense RNA, RNAi and artificial microRNA. Transgenics in B. juncea were developed following Agrobacterium-mediated transformation. From a total of 1232 independent T(0) transgenic events obtained using eight silencing constructs, 25 homozygous lines showing single gene inheritance were identified in the T(2) generation. Reduction of seed sinapine content in these lines ranged from 15.8% to 67.2%; the line with maximum reduction had sinapine content of 3.79 mg/g of DSW. The study also revealed that RNAi method was more efficient than the other two methods used in this study.